Eating disorders in minority ethnic populations in Australia, Canada, Aotearoa New Zealand and the UK: a scoping review - A. Williams-Ridgway; R. McGowan; S. McNeil; H. Tuomainen (Journal of Eating Disorders)
Abstract Background Historically, eating disorder (ED) research has largely focused on White girls and women, with minority ethnic populations underrepresented. Most research exploring EDs in minority ethnic populations has been conducted in the United States (US). The aim of this scoping review, the first of its kind, was to systematically examine research on disordered eating and EDs among minority ethnic populations in Australia, Canada, Aotearoa New Zealand and the United Kingdom (UK), four countries with shared sociocultural and healthcare characteristics. An inequity lens was applied to highlight gaps in research, access, and treatment experiences. Method Five databases (Medline, Embase, PsycINFO, CINHAL and Web of Science) were searched up to March 7, 2024. Two independent reviewers screened titles and abstracts and full texts against eligibility criteria resulting in the inclusion of 87 records (76 peer-reviewed articles and 11 theses). Included studies were charted according to their focus, study design, sample characteristics and findings, with a particular focus placed on prevalence, access to treatment and treatment experience. Results The majority of identified studies were conducted in the UK (61%, 53 studies). There was a notable lack of studies investigating assessment, diagnosis and intervention. Methodologies varied, though most studies utilised cross-sectional survey designs. Most samples were non-clinical, exclusively or predominantly girls and women, and focused on adolescents and young adults. Asian populations were the most frequently studied minority ethnic group. Understanding of prevalence and treatment experience amongst minority ethnic groups was limited. Conclusion There is a need for further research addressing inequities in ED prevalence, service access, and treatment experiences among minority ethnic and Indigenous groups, especially in Australia, Canada and Aotearoa New Zealand. Improved ethnicity data collection and culturally sensitive approaches to assessment, diagnosis and treatment are essential. Recommendations for future research and clinical practice are provided.